Analisis Efektivitas Program Relawan Pajak Dalam Meningkatkan Kepatuhan Pelaporan SPT Tahunan Orang Pribadi Di KPP Pratama Jakarta Cakung Tahun 2020-2022 - Ambarwati, Ambarwati; Nadiya, Nadiya; Chaerunisyah, Ana (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
The phenomenon in this research was that KPP Pratama Jakarta Cakung had implemented a volunteer tax program to facilitate the public in reporting their Annual Tax Returns (SPT). However, many individual taxpayers still needed to be made aware of their obligations to write their Annual Tax Returns. This study aimed to determine the effectiveness of the tax volunteer program in increasing the compliance of annual SPT reporting for individuals at KPP Pratama Jakarta Cakung and to find out the efforts and obstacles in implementing the volunteer tax program. This study employed a descriptive qualitative research method. The data collection techniques from this study were interviews, observation, and documentation. The study results showed that the tax volunteer program has effectively increased compliance with annual SPT reporting for individuals at KPP Pratama Jakarta Cakung. However, it has yet to be able to improve taxpayer compliance. It could be seen from the compliance ratio of individual taxpayers, which was still very low due to the lack of knowledge and awareness of taxpayers in reporting their Annual Tax Returns promptly, many taxpayers who were concerned about the confidentiality of financial information, and the disruptions on the DGT Online server. Several efforts made by KPP Pratama Jakarta Cakung were the tax volunteers and tax extension officers should get closer to taxpayers by providing outreach and information so the taxpayers report their Annual SPT on time; providing professional and trustworthy services, and making improvements to the DGT Online server